Pemberian Limbah Biogas Kotoran Sapi dan Mulsa Mucuna bracteata Pada bibit kelapa sawit (Elaeis guineensis Jacq.) Di Pembibitan Utama - Saputra, Sukemi Indra; ', Suhendarisman '; ', Sampoerno ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The process of developing oil palm cultivation is closely related to the availaibility of quality seed. Quality seed really determines the growth and production of commodities. The giving of biogas waste and mulch mucuna bracteata into the ground can inprove nutrient both macro and micro. The purpose of the research is to know influence from giving of waste biogas and mulch mucuna bracteata, and its interaction as well to determine the best combination on the grownth seeds palm oil plantations in a main nursery. This Research is done by using Completely Randomized Design experiment consisting two factor: biogas waste cow dug consisting four levels , mulch mucuna bracteata three levels and repetition.the reseach result shows the giving of biogas waste on palm seed influences on height,leaves,hump diameter ,palm seed leaf increase.interaction of waste biogas and mulch mucunan bracteata that is getting high of its dose can improve increase of levels, hump diamear growth ,height and palm seed leaf. The giving of biogas waste liquit 200 ml/plant and mulch mucuna bractea gives highest palm seed growth. Key words: palm, waste biogas and mulch mucuna bracteata